2002
DOI: 10.1042/bj3610557
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the integrases of human immunodeficiency viruses type 1 and type 2 by reverse transcriptases

Abstract: We present evidence that the integrases (INs) of HIV types 1 and 2 are inhibited in vitro by the reverse transcriptases (RTs) of HIV-1, HIV-2 and murine leukaemia virus. Both 3′-end processing and 3′-end joining (strand transfer) activities of IN were affected by the RTs. Full inhibitions were accomplished with most RT and IN combinations tested at around equimolar RT/IN ratios. The disintegration activity of IN was also inhibited by RTs. Neither DNA synthesis nor the ribonuclease H (RNase H) domain of RT were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 0 publications
2
42
0
Order By: Relevance
“…LEDGF 402-411 inhibited the enzymatic activity of IN more potently than LEDGF 361-370 did, although its affinity to IN was 3-fold weaker. This observation is because binding affinity is not the only factor that is responsible for the inhibitory activity of a molecule (K D and K i are different in many cases), as was shown for the RT inhibitors (36,37). The peptides inhibit integration in cells, do not lower the amounts of reverse transcripts, but do reduce the number of proviral copies and HIV-1 Tat-mediated transcription, showing that the peptides do not affect the early, but do halt the late, events of HIV-1 replication.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…LEDGF 402-411 inhibited the enzymatic activity of IN more potently than LEDGF 361-370 did, although its affinity to IN was 3-fold weaker. This observation is because binding affinity is not the only factor that is responsible for the inhibitory activity of a molecule (K D and K i are different in many cases), as was shown for the RT inhibitors (36,37). The peptides inhibit integration in cells, do not lower the amounts of reverse transcripts, but do reduce the number of proviral copies and HIV-1 Tat-mediated transcription, showing that the peptides do not affect the early, but do halt the late, events of HIV-1 replication.…”
Section: Discussionmentioning
confidence: 96%
“…The 3Ј end processing and the strandtransfer activities of IN were performed as previously described (36,37).…”
Section: Methodsmentioning
confidence: 99%
“…19,20 In contrast, Hehl et al have shown that with different assay and buffer conditions, RT at different molar ratios enhances strand transfer. 21 As a result, we were interested in how RT behaved in our HITS™ assay.…”
Section: Reverse Transcriptase Inhibits Integrationmentioning
confidence: 99%
“…This result agrees with the previously published data. 19,20 Since the activity of IN might be different at physiological temperature, we checked the effect of preincubation of the reaction at 37°C, using the microplate assay. In contrast to what we observed with preincubation of IN with DNA at 4°C, RT did not block integration when IN was preincubated with DNA at 37°C for 5 min.…”
Section: Reverse Transcriptase Inhibits Integrationmentioning
confidence: 99%
“…For example, it has been reported that NCp7 might influence the coupled joining by promoting DNA distortion (16) and that reverse transcriptase might play a role in blocking the auto-integration process (17). Host proteins, upon association with IN, have also been reported to improve in vitro viral DNA integration.…”
Section: Hiv-1 1 Integrase (In) Is An Essential Component Required Fomentioning
confidence: 99%